Process analysis of regional aerosol pollution during spring in the Pearl River Delta region, China. (December 2015) - Fan, Qi; Lan, Jing; Liu, Yiming; Wang, Xuemei; Chan, Pakwai; Hong, Yingying; Feng, Yerong; Liu, Yexin; Zeng, Yanjun; Liang, Guixiong
Abstract: A numerical simulation analysis was performed for three air pollution episodes in the Pearl River Delta (PRD) region during March 2012 using the third-generation air quality modeling system Models-3/CMAQ. The results demonstrated that particulate matter was the primary pollutant for all three pollution episodes and was accompanied by relatively low visibility in the first two episodes. Weather maps indicate that the first two episodes occurred under the influence of warm, wet southerly air flow systems that led to high humidity throughout the region. The liquid phase reaction of gaseous pollutants resulted in the generation of fine secondary particles, which were identified as the primary source of pollution in the first two episodes. The third pollution episode occurred during a warming period following a cold front. Relative humidity was lower during this episode, and coarse particles were the major pollution contributor. Results of process analysis indicated that emissions sources, horizontal transport and vertical transport were the primary factors affecting pollutant concentrations within the near-surface layer during all three episodes, while aerosol processes, cloud processes, horizontal transport and vertical transport had greater influence at approximately 900 m above ground. Cloud processes had a greater impact during the first two pollution episodes because of the higher relative humidity. In addition, by comparing pollution processes from different cities (Guangzhou and Zhongshan), the study revealed that the first two pollution episodes were the result of local emissions within the PRD region and transport between surrounding cities, while the third episode exhibited prominent regional pollution characteristics and was the result of regional pollutant transport. Highlights: The contributions of various physical and chemical processes to PM2.5 were quantified. The aerosol characteristics and their formation mechanisms during spring were explored. The contribution of local emissions and foreign sources from different cities to PM2.5 was analyzed.